2020
DOI: 10.1016/j.janxdis.2020.102327
|View full text |Cite
|
Sign up to set email alerts
|

Worry, avoidance, and coping during the COVID-19 pandemic: A comprehensive network analysis

Abstract: Highlights Conducted a network analysis of COVID-19-related worry, avoidance, and coping. The network consisted of three major hubs, replicated across gender and age groups. The most important hub centered around worries about the dangerousness of COVID-19. Belief that the COVID-19 threat is exaggerated formed the core of the second hub. Compulsive checking and reassurance-seeking defined the third most important hub.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
133
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 14 publications
14
133
0
7
Order By: Relevance
“…As reported by Taylor, Landry, Paluszek, Rachor et al (2020) in this volume, the COVID Stress Syndrome (defined dimensionally in terms of the degree of severity) appears to be at the center of a larger network of pandemic-relevant mental health constructs, with negative connections (i.e., negative correlations) with beliefs that pandemic-related threat is exaggerated and disregard for public health recommendations, and positive connections with self-protective behaviors. The findings from studies focused on posttraumatic stress symptoms and putative PTSD in response to COVID-19, as well as studies of health-related obsessions and compulsions, may be best understood in the context of a multifaceted network of pandemic-related distress.…”
Section: In Search Of a Comprehensive Model Of Pandemic-related Mentamentioning
confidence: 86%
See 1 more Smart Citation
“…As reported by Taylor, Landry, Paluszek, Rachor et al (2020) in this volume, the COVID Stress Syndrome (defined dimensionally in terms of the degree of severity) appears to be at the center of a larger network of pandemic-relevant mental health constructs, with negative connections (i.e., negative correlations) with beliefs that pandemic-related threat is exaggerated and disregard for public health recommendations, and positive connections with self-protective behaviors. The findings from studies focused on posttraumatic stress symptoms and putative PTSD in response to COVID-19, as well as studies of health-related obsessions and compulsions, may be best understood in the context of a multifaceted network of pandemic-related distress.…”
Section: In Search Of a Comprehensive Model Of Pandemic-related Mentamentioning
confidence: 86%
“…Stemming from the development of the COVID Stress Scales ( Taylor, Landry, Paluszek, Fergus et al, 2020 ), we found that distress-related responses to COVID-19 comprise a multi-faceted network of interconnected symptoms, which we called the COVID Stress Syndrome ( Taylor, Landry, Paluszek, McKay et al, 2020 ). This syndrome--anchored by COVID-19 danger and contamination fears at its core and with connections to fear of adverse socio-economic consequences, xenophobia, traumatic stress symptoms, and checking and reassurance seeking--is associated with panic buying, excessive avoidance of public places, and maladaptive attempts at coping (e.g., over-eating and increased consumption of alcohol and drugs) ( Taylor, Landry, Paluszek, Rachor, & Asmundson, 2020 ; Taylor, Landry, Paluszek, McKay et al, 2020 ).…”
Section: From Coronaphobia To Covid Stress Syndromementioning
confidence: 99%
“…COVID-19 poses significant challenges for many that would be expected to result in an increase in OC symptoms across different dimensions. COVID-19 has been previously been noted to have negative effects on mental health due to increased levels of uncertainty and unpredictability ( Tull et al, 2020 ; Wheaton et al, 2021 ; Zandifar & Badrfam, 2020 ), distress, fear, anxiety ( Elhai, Yang, McKay, & Asmundson, 2020 ; Mertens, Gerritsen, Duijndam, Salemink, & Engelhard, 2020 ), and health-related worries and concerns ( Jungmann & Witthöft, 2020 ; Taylor et al, 2020b ). Indeed, when OC symptoms emerge in community individuals due to the COVID-19 ( Zheng, Xiao, Xie, Wang, & Wang, 2020 ), it is not surprising to find an increase in symptoms across multiple dimensions in patients with OCD, especially in those with pre-existing OCD than those recently diagnosed with OCD ( Nissen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The final aim was to investigate how anti-mask attitudes are related to attitudes and behaviors that are associated with non-adherence to other pandemic-control measures during the COVID-19 pandemic, such as disregard for social distancing and anti-vaccination attitudes. Recent research provides evidence for a COVID-19 disregard “syndrome” [ 52 ]. This is not a syndrome in the medical sense of the term, but rather a constellation of inter-related attitudes and beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…This is not a syndrome in the medical sense of the term, but rather a constellation of inter-related attitudes and beliefs. People with this syndrome tend to (a) believe that the COVID-19 pandemic has been exaggerated, (b) see themselves as physically robust to any illness they may experience as a result of being infected with SARSCoV2, and (c) tend to disregard social distancing because they see it as unnecessary [ 52 ]. This syndrome is also associated with negative attitudes toward a potential vaccine for SARSCoV2 (i.e., beliefs that a vaccine is unnecessary or that the benefits of such a vaccine are outweighed by the potential risks) [ 52 ].…”
Section: Introductionmentioning
confidence: 99%